Housing Matters - Hammam, Sonia (World Bank, Washington, DC, 2014)
Housing matters to the livability of cities and to the productivity of their economies. The failure of cities to accommodate the housing needs of growing urban populations can be seen in the proliferation of poorly serviced, high-density informal settlements. Such settlements are not new in the history of rapidly growing cities, their persistence results as much from policies as from economics and demographic transition. Slums have attracted most of the attention on urban housing in developing countries, and the Millennium Development Goals have given prominence to their reduction. However, urban housing issues transcend conditions in slums and are linked closely to economic activity. City economies influence housing demand, and in turn the flexibility of housing supply affects economic activity and city growth. This paper provides an overview of the policy and institutional building blocks that determine housing sector performance, drawing on studies from both developed and developing countries. It focuses on property rights, including tenure choice, housing finance, and subsidies. It also reviews the factors that affect supply: the availability of serviced land, as well as land and housing regulations. While these elements have been standard tools of housing policy, they are still the subject of considerable debate over their sequencing, policy content, and priority. There has been a great deal of emphasis over the last two decades on demand-side measures to improve property rights systems, develop housing finance, and even to introduce new subsidy systems. All these developments are important, but as this paper argues, less progress has been made in understanding and addressing the factors that constrain supply, which often thwart improvements on the demand side.